The effects of job creation schemes on the unemployment duration in East Germany - Reinhard Hujer; Christopher Zeiss (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2006)
Job creation schemes have been one of the most important programmes of active labour market policy in Germany throughout the 1990s and into the first decade of the new century. A number of studies have analysed the effects of job creation schemes in Germany, presenting an overall disappointing picture. JCS seem to perform poorly in improving the employability or the chances of leaving unemployment for the participating individuals. The study extends the existing literature by an evaluation of JCS with the timing-of-events methodology in the duration context using administrative data for East Germany. The analysis is based on a multivariate mixed proportional hazard rate model that accounts for observable and unobservable characteristics. The results show that JCS increase the individual unemployment duration of the participants. The negative effect results from a locking-in effect and a strong negative effect after the programme has finished. Therefore, the results suggest that JCS do not improve the employment prospects for the participants.
Keywords: J68; C14; C41; H43; 330; Arbeitsbeschaffungsmaßnahme; Beschäftigungseffekte; Arbeitslosigkeitsdauer; Beschäftigungsfähigkeit; Arbeitsmarktchancen; Arbeitslose; berufliche Reintegration; IAB-Bewerberangebotsdatei; Beschäftigtenstatistik; IAB-Maßnahmeteilnehmergrunddatei; Ostdeutschland; Bundesrepublik Deutschland; Arbeitsbeschaffung; Berufliche Integration; Arbeitslosigkeit; Zeit; Beschäftigungseffekt; Schätzung; Neue Bundesländer; Deutschland